2022
DOI: 10.1186/s12890-022-01918-y
|View full text |Cite
|
Sign up to set email alerts
|

The significance of serum S100 calcium-binding protein A4 in silicosis

Abstract: Background Silicosis is a chronic occupational pulmonary disease characterized by persistent inflammation and irreversible fibrosis. Considerable evidences now indicate that S100 calcium-binding protein A4 (S100A4) has been associated with fibrotic diseases. However, the role of S100A4 in silicosis is still unclear. Methods In this study, serum levels of S100A4, transforming growth factor-β1 (TGF-β1), connective tissue growth factor (CTGF), interle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…S100A4, as an effective trigger of inflammatory process, can induce the release of cytokines and growth factors under different pathological conditions. 12,21,22 More and more researchers reported that S100A4 was associated with allergic inflammation and there was no distinction of the effect of S100A4 inside and outside cells. 14,[23][24][25] An increase of S100A4 in BALF in asthmatic mice and patients was also found, but the mechanism was not explored.…”
Section: Discussionmentioning
confidence: 99%
“…S100A4, as an effective trigger of inflammatory process, can induce the release of cytokines and growth factors under different pathological conditions. 12,21,22 More and more researchers reported that S100A4 was associated with allergic inflammation and there was no distinction of the effect of S100A4 inside and outside cells. 14,[23][24][25] An increase of S100A4 in BALF in asthmatic mice and patients was also found, but the mechanism was not explored.…”
Section: Discussionmentioning
confidence: 99%